Nursing students' evaluation of clinical learning environment and supervision models before and during the COVID-19 pandemic: a comparative study - Ferri, Paola; Stifani, Serena; Morotti, Elena; Alberti, Sara; Vannini, Valeria; Di Lorenzo, Rosaria; Rovesti, Sergio; Palese, Alvisa (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The COVID-19 pandemic has required a rapid reorganization of clinical training and supervision models for nursing education. The aim of this study was to compare students' levels of perception of the quality of the Clinical Learning Environment (CLE) using two different clinical supervision models.Methods: A comparative design was implemented. A convenience sample of second and third-year undergraduate nursing students (n=127) in clinical training in the 2018/2019 Academic Year (AY) received the usual nursing staff supervision model, while during the COVID-19 pandemic in the following year, they (n=69) received an individualized supervision model. Data were collected using three instruments: the Clinical Learning Environmental Quality Evaluation Index (CLEQI); the Clinical Learning Environment, Supervision and Nurse Teacher Scale (CLES+T); and a socio-demographic tool.Results: The mean total scores of both scales had increased in the second survey (CLEQI: M=57.88±11.8 vs. M=60.88±9.3, p=0.035; CLES+T: M=148.4±23.3 vs. M=154.5±21.9, p=0.037). The nursing students reported high levels of CLE quality with both supervision models, even though the individualized supervision model was rated significantly higher by the students than the staff supervision model. Conclusions: Students supported by a personal supervisor during clinical training had a more positive experience and rated the quality of the tutorial strategies, learning opportunities, safety and nursing care, leadership style of the ward manager and overall CLE more highly.